Cytomegalovirus is a potential risk factor for late‐onset hemorrhagic cystitis following allogeneic hematopoietic stem cell transplantation. Issue 1 (15th October 2013) - Han, Ting‐Ting; Xu, Lan‐Ping; Liu, Dai‐Hong; Liu, Kai‐Yan; Fu, Hai‐Xia; Zhao, Xiang‐Yu; Zhao, Xiao‐Su; Huang, Xiao‐Jun
<x xml:space="preserve">Abstract</x> Late‐onset hemorrhagic cystitis (LOHC) is a common complication following allogeneic hematopoietic stem cell transplantation (allo‐HSCT) and is primarily associated with viral infection. We prospectively quantified cytomegalovirus (CMV), BK virus (BKV), and adenovirus in urine and plasma using Q‐RT‐PCR in 50 consecutive patients to define the relationship between virus and LOHC. Of the 50 patients, 21 developed LOHC at a median of 29 days (range 4–64 days), with a cumulative incidence of 42% (±7.1%). The cumulative incidence of LOHC on day 100 in patients with and without CMV viremia (prior to or at the onset of LOHC) were 56.3% (±8.9%) and 16.7% (±9.1%) (P = 0.018), respectively, and it was 59.3% (±9.8%) and 21.7% (±8.8%) in patients with and without CMV viruria (prior to or at the onset of LOHC) (P = 0.021), respectively. The cumulative incidence of LOHC was also higher in patients with a plasma BKV load increased ≥3 log10 or with a urine BKV load increased ≥4 log10 than those without the increase (P < 0.001). Only one patient with LOHC was tested positive for ADV. Both the univariate and multivariate analyses showed that CMV viremia (HR = 3.461, 95% CI: 1.005–11.922, P = 0.049) and a plasma BKV load that was increased ≥3 log10 (HR = 10.705, 95%CI: 2.469–46.420, P = 0.002) were independent risk factors for the development of LOHC. We conclude that both CMV viremia and an increase of plasma BKV are independent risk factors for LOHC. And the role of CMV viremia was firstly demonstrated. Am. J. Hematol. 89:55–61, 2014. © 2013 Wiley Periodicals, Inc.